Estudio de factibilidad para el lanzamiento de un paquete de beneficios de atención médica para diabéticos en el Punto Médico Familiar Italia en la ciudad de Quito - Rodríguez Constante, María Belén (2013)
In this project assessed feasibility to developing in the market a comprehensive medical benefits package for patients suffering the Diabetes, which has been considered vulnerability by the medical insurance industry. So we have seen the great need to launch a full service for patients suffering from this disease. This package includes the following services: Internal Medicine, Endocrinology, Nutrition and Ophthalmology, additional laboratory tests will be done to monitor the patient for all the year.